Perceptions of crime and the built environment: the case of the Bloemfontein Central Business District (CBD) - Hoogendoorn, Gijsbert (Acta Structilia, 2008)
Internationally, inner-city crime has been a well-documented area of urban studies. In South African urban discourse, however, crime studies and inner-city crime studies per se have been scant. Therefore, it is the aim of this article to address the paucity of academic reflection, in this regard in South Africa, by means of a case study on the spatial patterns of crime distribution, perceptions of crime, and fear of crime in the inner city of Bloemfontein, and how these factors influence urban morphology (and vice versa). This case study on one of South Africa’s middle-order cities may potentially comprise a valuable contribution, since the majority of inner-city studies on crime thus far have focused predominantly on the three major metropolitan areas of South Africa. Therefore, three arguments shall be put forward. Firstly, the impact of decentralised shopping centres on the prevalence of crime in inner cities will be highlighted. Secondly, the relationship between crime and ‘grime’ (physical decay and neglect) as causal factors in inner-city areas will be discussed. Thirdly, it will be argued that the fear of crime in the inner-city is an important consideration to be taken into account when assessing the spatial patterns and perceptions of this occurrence. In the case of Bloemfontein, this fear does not seem to be only racially related as black and white people experience the same levels of fear. By means of these arguments, an attempt will be made to contribute to the understanding of inner-city crime and its relationship to the urban form